Students Perception of Erlangga Book Reader Application in Listening Skill: Persepsi Siswa Terhadap Aplikasi Pembaca Buku Erlangga dalam Keterampilan Menyimak - Safitri, Elisa Bella; Santoso, Dian Rahma (Universitas Muhammadiyah Sidoarjo, 2023)
Globalization Era presents a fun context through the use of application technology on mobile phones as a method of learning English in listening skills. such as the use of the Erlangga book reader application on listening skills, based on student perceptions. Erlangga Book Reader is an iOS and Android-based application to play multimedia content from Erlangga Book Publishers using a QR Code. The purpose of this study was to determine students' perceptions of the Erlangga Book Reader application on listening skills. This research uses qualitative research. Data collection techniques using a questionnaire. The results showed that students' perceptions of the Erlangga Book Reader had a significant effect on students' listening comprehension, although there were some difficulties felt by students. This can be seen from the results of the questionnaire given to 3rd grade students randomly as many as 20 respondents, from 10 questions that were answered.